A longitudinal study of hepatitis C virus testing and infection status notification on behaviour change in people who inject drugs. Issue 8 (26th March 2015) - Spelman, T; Morris, M D; Zang, G; Rice, T; Page, K; Maher, L; Lloyd, A; Grebely, J; Dore, G J; Kim, A Y; Shoukry, N H; Hellard, M; et al.
Abstract : Background: Hepatitis C virus (HCV) testing and counselling have the potential to impact individual behaviour and transmission dynamics at the population level. Evidence of the impact of an HCV-positive status notification on injection risk reduction is limited. The objective of our study was to (1) assess drug and alcohol use and injection risk behaviours following notification; (2) to compare behaviour change in people who inject drugs (PWID) who received a positive test result and those who remained negative; and (3) to assess the effect of age on risk behaviour. Methods: Data from the International Collaboration of Incident HIV and HCV Infection in Injecting Cohorts (InC3 Study) were analysed. Participants who were initially HCV seronegative were followed prospectively with periodic HCV blood testing and post-test disclosure and interview-administered questionnaires assessing drug use and injection behaviours. Multivariable generalised estimating equations were used to assess behavioural changes over time. Results: Notification of an HCV-positive test was independently associated with a small increase in alcohol use relative to notification of a negative test. No significant differences in postnotification injection drug use, receptive sharing of ancillary injecting equipment and syringe borrowing postnotification were observed between diagnosis groups. Younger PWID receiving a positive HCV test notification demonstrated a significant increase in subsequent alcohol use compared with younger HCV negative. Conclusions: The proportion of PWID reporting alcohol use increased among those receiving an HCV-positive notification, increased the frequency of alcohol use postnotification, while no reduction in injection drug use behaviours was observed between notification groups. These findings underscore the need to develop novel communication strategies during post-test notification to improve their impact on subsequent alcohol use and risk behaviours.